The Effects of Speech Acts towards Behavior in Real Steel Movie - Raditya Syamria Maryani; Adi Prautomo; Waladdin Panggabean (Faculty of Letters Universitas Balikpapan, 2022)
This research aims to find the types of speech acts and to explain how the effect toward behavior of main character in Real Steel movie. The researcher uses speech act theory by Austin and Searle to discuss the type and effect toward behavior of the main character in the movie. The method used in this research is qualitative method that explained descriptively. Qualitative research is a research conducted with the source of data that comes in form of writing and descriptive means that the researcher would describe the collected data descriptively throughout the thesis. The results found the types of speech acts namely locution, illocution, and perlocution. locution consists of five classifications, Illocution itself consists of five types, namely assertive, descriptive, commissive, expressive, and declaration. While perlocution itself consists of twelve types, but the researcher only found five types contained in the dialogue to convince the listener, scare the listener, to remind the listener, to make the listener do something, and to make the listener aware of something. As for the effect on behavior, the researcher concludes in two parts, namely whether includes in a positive effect or negative effect on the behavior of the speaker or speech partner.